Application of Statecharts in Buck-Boost DC-DC Converter Simulation - Cendoya, Marcelo Gustavo (2021)
A very attractive and relatively simple option to simulate a DC-DC converter is to use a hybrid model. In this case, the need to use very small simulation steps (as those necessary to simulate models carried out at the physical level) is avoided. Furthermore, unlike the averaged state-space models, it has the advantage that the model is valid throughout the entire working range of the converter and for both conduction modes (continuous and discontinuous). By simulating several renewable energy conversion systems incorporating DC-DC converters, the authors have discovered the true potential of this modeling method. Despite its inherent advantages, this approach to DC-DC converters simulation is not as widely adopted as it should be. This work tries to encourage the reader of its use in certain typical situations. In this article the implementation of the hybrid model of the DC-DC Buck-Boost converter, using Statechart techniques, is performed. This model was written in the Stateflow language, a tool from the MATLAB®/Simulink environment, and allowed the creation of a building block formed by the described converter model with adequate interfaces to the SimPowerSystem and Simulink environments. The block is validated by comparing simulation results, realized under different operating conditions, with calculations done employing well-known and proven formulas. As an example of the use of the presented block, a buck-boost DC-DC converter with voltage and current control loops is simulated, corroborating its correct performance.